Management Ethics for Islamic Development Institutions in Malaysia: An Approach of Hisbah - Ibrahim, Azrin; ., . (International Journal of Engineering and Technology, 2018)
The purpose of this study is to examine and highlight hisbah as a management ethical approach for Islamic development institutions. Generally, each institutions has its own ethic that has been gazette. However, this study attempts to emphasize hisbah as an approach in management ethics to be emphasized in the Islamic development institutions. This is because hisbah is a supervisory method born from Islamic epistemology and also practiced by the Prophet Muhammad SAW. Hisbah is also a holistic ethic because its application encompasses internal and external surveillance within each person. In addition, hisbah method also emphasizes the relationship between humankind and Allah SWT, human beings and human beings with natural resources. However, some issues must be resolved. What are the definitions and components contained in hisbah? How hisbah can be practiced as a management ethic for Islamic development institutions? This study is generally aimed to addressing these issues. This study applies descriptive research design and document study as a means of collecting data. Finally, this study found that hisbah has several components to be implemented as the ethical management for Islamic development institutions. In addition, the study also found that the adoption of hisbah as ethical in Islamic development institutions would create more disciplined, proactive and good employees as well as able to boost the performance of institutions to better performance. Â Â Â